Impulsive choice predicts short-term relapse in substance-dependent individuals attending an in-patient detoxification programme. Issue 10 (July 2015) - Stevens, L.; Goudriaan, A. E.; Verdejo-Garcia, A.; Dom, G.; Roeyers, H.; Vanderplasschen, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Impulsivity is a hallmark characteristic of substance use disorders. Recently, studies have begun to explore whether increased impulsivity in substance-dependent individuals (SDIs) is associated with a greater propensity to relapse following treatment. Despite growing recognition of its multidimensional nature, however, most studies have treated impulsivity unilaterally. Accordingly, it remains unclear whether certain facets of impulsivity are more relevant to relapse than others. The aim of the current study was to examine the relationship between multiple facets of impulsivity and short-term relapse in SDIs. As a secondary aim, we explored the role of treatment retention in this relationship. Method A personality-based impulsivity questionnaire (UPPS) and three neurocognitive tasks of impulsivity [stop-signal task (SST), delay discounting task (DDT) and Iowa gambling task (IGT)] were administered in a heterogeneous sample of 70 SDIs shortly following their entry in an in-patient detoxification programme. Mediation analyses were performed to explore whether the effects of impulsivity on relapse were mediated by treatment retention. Results Performance on two neurocognitive indices of impulsive choice (i.e. delay discounting and impulsive decision-making) significantly predicted short-term relapse. The effects of delay discounting and impulsive decision-making on relapse propensity were mediated by treatment retention. Conclusions Neurocognitive indices of impulsivity may be more sensitive to the prediction of relapse than trait-based self-report questionnaires. Post-treatment relapse in SDIs may be reduced by targeting the processes involved in impulsive choice and by improving treatment retention in SDIs with inflated impulsivity.